2009
DOI: 10.1002/mnfr.200800493
|View full text |Cite
|
Sign up to set email alerts
|

Hop bitter acids efficiently block inflammation independent of GRα, PPARα, or PPARγ

Abstract: Hop (Humulus lupulus L.) is an essential ingredient of beer, where it provides the typical bitter taste, but is also applied in traditional folk medicine for sedative and antibacterial purposes. In this study, we demonstrate and compare the anti-inflammatory effect of various classes of hop bitter acids (HBA), including alpha-acids (AA), beta-acids (BA), and iso-alpha-acids (IAA), in fibroblasts, which are important players in the inflammatory response. All three studied classes of HBA blocked the tumor necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 54 publications
(67 reference statements)
2
29
0
Order By: Relevance
“…Therefore, these results strongly suggest that tetrahydro iso -alpha acids exert beneficial effect on plasma glucose, inflammation and insulin resistance independently of body weight loss or lower body fat accumulation. In accordance with this hypothesis, it has been previously demonstrated that these compounds inhibit LPS–stimulated PGE 2 , TNF-α, IL-6, nitric oxide and COX-2 abundance, as well as NF-κB pathway [15][17]. It is worth noting that previous study has shown that mice treated for 21 days with Meta060 did not exhibited any changes in body weight gain and food intake [32], further supporting that these compounds are not acting through food intake and or body weight-dependent mechanisms.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Therefore, these results strongly suggest that tetrahydro iso -alpha acids exert beneficial effect on plasma glucose, inflammation and insulin resistance independently of body weight loss or lower body fat accumulation. In accordance with this hypothesis, it has been previously demonstrated that these compounds inhibit LPS–stimulated PGE 2 , TNF-α, IL-6, nitric oxide and COX-2 abundance, as well as NF-κB pathway [15][17]. It is worth noting that previous study has shown that mice treated for 21 days with Meta060 did not exhibited any changes in body weight gain and food intake [32], further supporting that these compounds are not acting through food intake and or body weight-dependent mechanisms.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, these compounds exert anti-inflammatory activity on LPS-stimulated tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6) production in isolated peripheral blood mononuclear cells [16]. In addition to these effects hops-derived compounds (including iso -alpha acids) have been found to block TNF-α-induced production of IL-6 and to inhibit the transactivation of NF-κB, activator protein-1 (AP-1), and cAMP-response element-binding protein (CREB) in fibroblasts [17]. More recently, it has been proposed that hops has positive impact on adipocyte metabolism [18] and glucose tolerance in obese and diabetic rodents; however, the exact mechanisms explaining these effects are not well characterized [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…GCs are already widely used in the clinic, but novel and more specific MSK1 and MAPK inhibitors should be developed to prevent off-target effects and to warrant the safety of the combination [80]. Another combination with potential for the clinic is the combination of GCs with hop bitter acids, the latter being natural compounds which have been shown to inhibit NF-B activation [81].…”
Section: Advantage Of Combinatorial Approaches?mentioning
confidence: 99%
“…Results of a population-based inflammation index based on literature-derived dietary intake and a panel of six inflammation markers found that alcohol intake at ~14 g/day was associated with decreased systemic inflammation (51), although sTNFRI and II were not included in the panel. Polyphenols such as resveratrol in red wine (52) and hops in beer (53) may contribute to an anti-inflammatory effect through inhibition of the transcription factor NF-κB (54). …”
Section: Discussionmentioning
confidence: 99%